Gene-enhanced tissue engineering for dental hard tissue regeneration: (1) overview and practical considerations - Edwards, Paul C (BioMed Central, 2006)
Gene-based therapies for tissue regeneration involve delivering a specific gene to a target tissue with the goal of changing the phenotype or protein expression profile of the recipient cell; the ultimate goal being to form specific tissues required for regeneration. One of the principal advantages of this approach is that it provides for a sustained delivery of physiologic levels of the growth factor of interest. This manuscript will review the principals of gene-enhanced tissue engineering and the techniques of introducing DNA into cells. Part 2 will review recent advances in gene-based therapies for dental hard tissue regeneration, specifically as it pertains to dentin regeneration/pulp capping and periodontal regeneration.